Oseltamivir–Resistant Pandemic H1N1/2009 Influenza Virus Possesses Lower Transmissibility and Fitness in Ferrets - Duan, Susu; Boltz, David A.; Seiler, Patrick; Li, Jiang; Bragstad, Karoline; Nielsen, Lars P.; Webby, Richard J.; Webster, Robert G.; Govorkova, Elena A. (PLOS Pathogens, 2010)
Author Summary Most of the currently circulating pandemic H1N1/2009 (“swine”) influenza viruses are susceptible to the anti-influenza drug oseltamivir. Many countries have stockpiled oseltamivir for pandemic preparedness, and to date only a small proportion of the H1N1/2009 viruses isolated have been oseltamivir-resistant. However, if these viruses can be readily transmitted, oseltamivir resistance may spread. We evaluated the transmissibility of a pair of pandemic H1N1/2009 influenza viruses in ferrets. One virus was oseltamivir-sensitive and the other carried the oseltamivir resistance-associated H275Y NA mutation. We also investigated the viruses' susceptibility to NA inhibitors (the drug class to which oseltamivir belongs), their NA enzyme kinetics, and their replication efficiency in cultured cells. Under identical conditions, the resistant H1N1/2009 virus was not transmitted by respiratory droplets but was efficiently transmitted by direct contact, while the sensitive H1N1/2009 virus was efficiently transmitted by both routes.